Hypotension after induction of general anesthesia: occurrence, risk factors, and therapy. A prospective multicentre observational study - Jor, Ondrej; Maca, Jan; Koutna, Jirina; Gemrotova, Michaela; Vymazal, Tomas; Litschmannova, Martina; Sevcik, Pavel; Reimer, Petr; Mikulova, Vera; Trlicova, Michaela; Cerny, Vladimir (Journal of anesthesia, 2018)
Background Hypotension after induction of general anesthesia (GAIH) is common in anesthesiology practice and can impact outcomes. Methods In this prospective multicenter, cross-sectional, observational study, the hypotension was defined as a decrease in mean arterial pressure of > 30% compared to the first measurement in the operation theatre before general anesthesia (GA) induction. Blood pressure was measured immediately at the time of endotracheal intubation ( T ETI ), at five ( T 5 ) and 10 ( T 10 ) minutes after. All subjects aged > 18 years undergoing elective non-cardiac surgery under GA were included. The goals were description of GAIH occurrence, the association of GAIH with selected comorbidities, chronic medications, and anesthetics with GAIH, and the type and efficacy of interventions used to correct hypotension. Results Data from 661 subjects, whose GA was induced with propofol and sufentanil, were analyzed. In 36.5% of subjects, GAIH was observed at ≥ 1 of the assessed time points. GAIH was present in 2.9% subjects at all time points. The probability of GAIH is raising with age, degree of hypertension at time of arrival to theatre and presence of diabetes. The type of volatile anesthetic was not associated with the occurrence of GAIH. The overall efficiency of interventions to correct hypotension was 94.4%. Bolus fluids were the most often used intervention and was 96.4% effective. Conclusion GAIH rate depends on age, degree of blood pressure decompensation prior the surgery, and presence of diabetes mellitus type II.